Prospects of Electronic Commerce in India - Bansal, Rashmi (Journal of Asian Business Strategy, 2013)
This article aims to analyse various socio-cultural factors such as urban-rural digital divide, regional languages, customs, geographical locations and transport and logistics that affect the development of the electronic commerce in India vis-à-vis the global scenario. During the last decade, the internet and mobile services have seen a phenomenal growth, both horizontal as well as vertical. The penetration ratio of the broadband in homes in India is fast increasing. The scenario of electronic commerce in India presents a study in contrast due to approximately 69 per cent population living in the villages. However, the segment of the population living in metros and sub-metros is also quite large and affluent and surpasses the total e-commerce markets of many developed countries. Due to this reason, the online shopping in India is catching up. Nevertheless, there are different driving forces as well as barriers which have been identified. The most important driving force for e-shopping is time saving while the most prominent barrier is the doubt about the quality of the product. Insecurity of the electronic transaction is also an important inhibitor. With the current security steps being taken by the government of India and also at the technological level, it is hoped that these fears would be allayed and prospects of e-commerce in India appear to be bright.